The acquisition of object clitic pronouns in Heritage Romanian - Pirvulescu, Mihaela; Hill, Virginia (Frontiers in Language Sciences, 2025)
This paper examines the acquisition of object clitic pronouns in Heritage Romanian (HR) by school-age children in Toronto who are second-generation speakers of Romanian—i.e., children of first-generation immigrant parents. These children have been exposed to Romanian as their first language (L1) since birth within the home, while English has served as the societal language, primarily encountered outside the home. Additionally, they were enrolled in French immersion programs between the ages of 3 and 6. This study looks at both production and comprehension of preverbal object clitic pronouns. The findings demonstrate that HR exhibits similar patterns in the domain of object clitics as those observed in Romanian-dominant trilingual children, particularly regarding clitic omissions at specific developmental stages. Moreover, HR shares characteristics commonly identified in bilingual (heritage) language acquisition, such as gender errors. Overall, this study provides further evidence that both language use and literacy play a crucial role in shaping heritage language proficiency.